2018
DOI: 10.1097/iop.0000000000001137
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Thyroid Eye Disease: Clinical Characteristics and Orbital Decompression Outcomes

Abstract: Pediatric TED patients exhibit mild symptoms, such as proptosis and eyelid retraction without strabismus, vision loss, or optic neuropathy. Some children with TED have severe disfigurement and corneal exposure due to the disease and benefit from orbital decompression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 14 publications
2
5
0
Order By: Relevance
“…The results of our study showed that proptosis was the most frequent clinical sign of paediatric GO followed by eyelid retraction and eyelid swelling, which is in line with the data published by Chua et al. (2018). Durairaj et al.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The results of our study showed that proptosis was the most frequent clinical sign of paediatric GO followed by eyelid retraction and eyelid swelling, which is in line with the data published by Chua et al. (2018). Durairaj et al.…”
Section: Discussionsupporting
confidence: 93%
“…To our knowledge, this study represents the largest cohort of paediatric GO patients published to date. The gender distribution of our patients is similar to most of other studied cohort of paediatric GO patients, males being outnumbered (Goldstein et al 2008;Lim et al 2014;Chua et al 2018).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Decompression surgery is best deferred until the facial skull has fully grown. Success rates are the same as in adults ( 85 , 86 ).…”
Section: Pediatric Graves’ Orbitopathymentioning
confidence: 99%